The GlucoCoper – An Exploratory Study to Assess Coping Mechanisms of Women Diagnosed with Diabetes Mellitus. Issue 1 (2019) - Kalra, Bharti; Kalra, Sanjay; Balhara, Yatan Pal Singh; Verma, Komal; Azam, AAS; Shaikh, Fouzia A
No abstract available